2012 American Society of Clinical Oncology and American Society of Hypertension: 27th Annual Scientific Meeting and Exposition - Alexander, Walter (MediMedia USA, Inc., 2012)
Selected ASCO topics include drugs for melanoma, gastrointestinal tumors, non–small-cell lung cancer, and advanced breast cancer. ASH presentations cover ambulatory blood pressure in type-2 diabetes, triple therapy in obese patients, the effect of body mass on cardiovascular outcomes, and a novel glucagon-like peptide agonist for diabetes.